Biophysical Properties of Inner Bark and Sapwood in Tree Species From Forests With Contrasting Precipitation in Subtropical South America - Carrasco, Laureano Oliva; Bucci, Sandra J.; Scholz, Fabian G.; Loto, Dante; Gasparri, Ignacio; Goldstein, Guillermo; Campanello, Paula I. (Frontiers in Forests and Global Change, 2022)
Sapwood capacitance and water storage are known to play an important role in the water economy of trees by acting as an intermediate water source for transpiring leaves. The bark, in addition to be involved in protection and mechanical support of the trees, can also serve as a water reservoir. We examined the relationship between bark and sapwood biophysical properties in tree species occurring in forests at the opposite ends of a moisture gradient in subtropical South America. We also assessed the relationships between wood density, growth rate and the magnitude of water reservoir use. The inner bark thickness varied between 1.89 cm to 0.50 cm across species and sites and there were not significant differences between forests. Inner bark capacitance of species from the dry forest was higher than sapwood capacitance, and the opposite was found in the moist forest. Sapwood capacitance (262±80.8 Kg m-3 MPa-1) was significantly higher in the moist forest compared to the dry forest (41.9±4.5 Kg m-3 MPa-1), while the opposite was found for inner bark (50.7± 8.4 and 83.1± 11.4 Kg m-3 MPa-1, respectively). Inner bark capacitance and density were linear and positively correlated across species, while for sapwood the relationship was well described by a negative exponential function. In species with higher percentage of inner bark, the time lags in the daily contractions of bark and sapwood tissues were lower. Relative growth rate was negatively correlated with inner bark and sapwood density and positively with daily stored water used and percentage of inner bark across species and sites. Our results suggest that sapwood is a relevant water storage tissue in the trees of the moist forest while inner bark is important for trees in the dry forest. High stem capacitance and water storage are needed to cope with short or seasonal periods of water deficit and for maintaining growth rates. These stem properties will be more relevant under climatic scenarios with more frequent extreme drought events or seasonal reduction in precipitation in these forest ecosystems.